Offshoring within South African manufacturing firms: An analysis of the labour market effects - Anmar Pretorius; Carli Bezuidenhout; Marianne Matthee; Derick Blaauw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
In South Africa, the manufacturing sector - important for growth and employment creation - has shown declining growth, poor productivity performance, decreased labour demand, and increased imports of intermediate goods (offshoring activities). Offshoring influences jobs and wages differently depending on the type of industry and worker. We provide a nuanced view of offshoring in South Africa, using firm- and employer-employee-level data to disentangle its impact on the labour market in terms of capital- and labour-intensive industries and skilled and unskilled workers. Contrary to previous findings in developed countries, we find that offshoring generally lowers employment in manufacturing firms, and seems to increase the percentage of unskilled workers and lower the percentage of skilled workers. There are indications that increased narrow offshoring increases the cohort of unskilled workers, particularly in ultra-labour-intensive industries. As offshoring gains momentum, worker-level earnings increase in capital- and labour-intensive industries but decrease in ultra-labour-intensive industries.
Keywords: F14; F16; 330; offshoring; firm-level data; employer-employee data; employment; skills; wages